2017
DOI: 10.1016/j.bjid.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pain in individuals infected by human T-cell lymphotropic virus type 1 (HTLV-1)

Abstract: The use of self-medication, physiotherapy and the presence of depression are independently associated with neurological symptoms in HTLV-1 infected patients. Religious practice and physical activity are both protective for the development of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Several reports have suggested that rheumatologic manifestations, such as arthralgia and lower back pain, have been observed in HTLV1 carriers [ 69 , 70 ]. Complaints of pain seem to be common among HTLV-1-infected individuals, regardless of neurological manifestations associated with HAM/TSP [ 71 ]. An epidemiologic systematic review and meta-analysis indicated an association between HTLV-1 infection and rheumatologic disorders, such as fibromyalgia and arthropathy, in HTLV-1 carriers [ 16 ].…”
Section: Are There Any Differences In Clinical Features Between Htlv-...mentioning
confidence: 99%
“…Tropical spastic paraparesis is a chronic disease in which pain is frequent, and it has been previously demonstrated that patients suffering from it generally have depressive and anxiety symptoms associated with chronic pain 4 . Therefore, the participant's psychiatric condition would influence the measurement of the questions' variables.…”
Section: Dear Editormentioning
confidence: 99%